2007
DOI: 10.1002/jsfa.3021
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic and in sacco methods to estimate rumen degradation of food protein in cattle

Abstract: Despite variations between in sacco and enzyme estimates for different foods, the relationships between these estimates suggest that the HLA enzyme method has the potential to estimate food degradation. Copyright © 2007 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The patterns of mean degradation with increasing time from 0 to 96 h for the fresh inocula also compared well with the published values of similar feeds that were tested in sacco in fistulated animals (AFRC, 1993;Chaudhry, 2007;Mohamed and Chaudhry, 2008). In fact the degradation of grass nuts in this study was similar to the earlier data for a different sample of the same batch of grass nuts (Chaudhry, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The patterns of mean degradation with increasing time from 0 to 96 h for the fresh inocula also compared well with the published values of similar feeds that were tested in sacco in fistulated animals (AFRC, 1993;Chaudhry, 2007;Mohamed and Chaudhry, 2008). In fact the degradation of grass nuts in this study was similar to the earlier data for a different sample of the same batch of grass nuts (Chaudhry, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…The residues were also analysed for nitrogen to estimate CP (N × 6.25) degradation (CPD). Triplicate samples of each pre-incubated feed were also analysed for DM, OM, CP, EE, NDF, and ADF by using appropriate methods as previously described by Chaudhry (2007).…”
Section: Incubation Of Feeds and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these methods have used solvents [1,2] or enzymes [3][4][5][6] instead of rumen fluid to study kinetics of rumen degradation. However, the validity of these methods depended upon the availability of either in sacco or rumen fluid based in vitro data for making comparisons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Proteases with different origins have been tested by some researchers to determine ruminal protein degradability. The most commonly used protease enzyme was the enzyme which has been extracted from Streptomyces griseus (Krishnamoorthy et al, 1983;Chaudhry, 2005Chaudhry, , 2007. Aufrere et al (1991) reported that in the French protein system (digestible proteins in the intestine, PDI), the enzymatic method is used as a laboratory method for nitrogen evaluation.…”
Section: Introductionmentioning
confidence: 99%